Sustainable ecotourism development and community involvement: a bibliometric analysis on research trends (2003 – 2024) / Reemina Narzary and Rajdeep Deb - Narzary, Reemina; Deb, Rajdeep (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
With the growing focus and recognition of ecological preservation all over the world, the concept of ecotourism is becoming popular, but the challenges it brings to the sustainable development in environment cannot be neglected. Therefore, to resolve such challenges, there is a need to conduct a thorough examination of how this field is evolving along with the review of the extant literature in the field of ecotourism. Besides, there is also a need to discuss the key issues to determine future research directions. To achieve this, a bibliometric review is performed to assimilate knowledge from a total of 149 journal articles listed in the Scopus database and published between 2003 and 2024 to analyse. Moreover, this study uses scientometrics tool to conduct a systematic review of research and development on ecotourism. The analysis involves network visualization and scientific mapping analysis which was created using open-source data visualization tool called VOSviewer. The study attempts to bring light on three research streams in the field: sustainable tourism, ecotourism development, community-based tourism. Furthermore, this study provides theoretical recommendations for future researchers on study related to sustainable ecotourism development.